Musow ka yiriwali sira dôyé kenike sènèye - International Institute of Tropical Agriculture (International Livestock Research Institute, 2018)
Episode seven of a radio program series by the Africa RISING program in Bambara dialect that is spoken in southern Mali. In this episode which aired on KAFO KAN radio on 1 December 2017, discussions focused on the gender dynamics prevailing within the community, particularly the role of women in sorghum farming. This radio program was produced as part of Africa RISING activity – Use of Interactive radio to scale-up agriculture and nutrition technologies in Africa RISING Mali.